THE INFLUENCE OF THE PYRAMID DISCUSSION TOWARDS THE STUDENT WRITING ABILITY - Nullah, Nazhan (JOLLT Journal of Languages and Language Teaching, 2018)
This research was aimed to know whether the " Pyramid Discussion" can give a significant influence toward the students' writing skill at the second year students’ of SMA Darul Hikmah in the Academic Year of 2016/2017. The research design of this study was pre-experimental design with pre-test and post-test one group only. The population of this research was the second grade student of SMA Darul Hikmah Mataram in the Academic Year of 2016/2017 that consist of 33 students with 18 males and 15 females students. Meanwhile, the instrument of this research was pre-writing test. The technique of data analysis were descriptive analysis and inferential analysis. Based on the result of the data analysis as the mean score of pre-test was 22.5 and the mean score of post-test was 28.2 Whereas the score of t-test was 9.24 the score of t-table was 1.68 with 32 of freedom degree it was the confidence level of 0.05 or 90% the findings indicated that the value of t-test was higher than the value of t-table (9.24 >1.684). The conclusion of this research showed that " Pyramid Discussion" was significantly influenced the students' writing skill at the second year students’ of SMA Darul Hikmah in the Academic Year of 2016/2017. It can be conferred that the null hypothesis (Ho) was rejected and therefore the alternative hypothesis (Ha) was accepted. Finally the researcher may conclude that the use of pyramid discussion in teaching writing was significantly influenced.